Students’ Ways of Understanding Academic Writing - Suciyati Sulaiman (MASI Mandiri Edukasi, 2022)
Universities have placed academic writing skills as valuable skills for university students; some universities have compulsory modules for undergraduates, and some have dedicated writing centers for students to seek assistance in composing academic writing. Without a doubt, writing in English, particularly for those whose first language is not English, is considered a complex and challenging skill to master. In addition, academic writing is even more complex, as an essential element of academic writing is the inclusion of claims and opinions. Therefore, the struggle observed is that students cannot voice their opinions in a formal writing context, which perhaps resulted in the structure of the written piece not being coherent and cohesive as per the standard of academic writing. In order to achieve its aim, this study will use a phenomenographic research approach to investigate the undergraduate’s conceptions of academic writing. A phenomenography approach is used in this study because students’ experience composing academic writing would be the focus, and the research object would look at the variation in ways of experiencing such phenomena. The study relates to learners from various faculties at the University with a common ground of their English language proficiency that is used to gain entry to the University.